PENGUJIAN SIFAT KIMIA DAN FISIKA AIRTANAH : TESTING THE CHEMICAL AND PHYSICAL PROPERTIES OF GROUNDWATER - BODIAN DAVIN PANGGABEAN BODIAN; Frans Simbol Tambing (JISTECH: Journal of Information Science and Technology, 2024)
Communities in Jayapura use groundwater for daily needs, whether obtained from springs, dug wells and drilled wells. The research was conducted in the Kotaraja, Ayapo and Aimbe areas. The aim of this research is to determine the chemical and physical properties of groundwater based on laboratory tests. The chemical and physical properties of groundwater are one of the main properties of water and are very useful for determining groundwater quality. This research took three locations with the sampling method carried out using stratified random sampling. The samples taken were springs and drilled wells. The groundwater chemical properties parameters tested include Calcium (Ca), Magnesium (Mg), Sodium (Na), Potassium (K), Bicarbonate (HCO3). Chloride (Cl), Sulfate (SO4), pH, TDS, and Hardness, while the physical property parameters of groundwater tested include color, odor, taste, and temperature (T0C). In general, all samples analyzed from the research area show that the levels of chemical elements in groundwater have not exceeded drinking water standard limits, but there are locations that have high hardness CaCO3 levels, namely at location Ka.01 (Kaliacai) at 343 mg/L and location Ay.02 (Ayapo) pH 9.32. The results of the physical properties test show that the test concentration values ​​have not exceeded the drinking water standard limits, meaning that the groundwater in the research area is suitable for use. Key words :Chemistry-physics, groundwater.